Data control and digital regulatory space(s): towards a new European approach - Roxana Radu; Jean-Marie Chenou (Internet Policy Review, 2015)
Data control, among the newest forms of power fostered by information and communication technologies (ICTs), triggers a continuous (re)negotiation of public and private orderings, with direct implications on both regulators and intermediaries. This article examines the stance of the European Union (EU) regarding the position of Google - the world's largest internet services company as per its 2014 market value - in two controversial instances: the 'right to be forgotten' and the implementation of EU competition rules. It provides an analysis of these evolving debates and their meaning for EU regulatory thrust more broadly, discussing the shift in the approach to digital markets and the proactive development of a European framework influential beyond continental boundaries.
Keywords: 300; Intermediary liability; Regulatory shifts; Digital monopoly; Right to be forgotten; E-commerce; Data protection; Taxation; Antitrust; Privacy